MODEL-INDEPENDENT EXTRACTION OF THE KΛp COUPLING CONSTANT - Mart, Terry (UI Scholars Hub, 2008)
We have extracted the kaon-hyperon-nucleon coupling constant by means of a model-independent method and recent experimental data on kaon photoproduction off a nucleon. The extracted coupling constant is consistent with the SU(3) prediction as well as with the values obtained from the kaon-nucleon scattering process.